2016
DOI: 10.3892/mco.2016.943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional intervention in head and neck cancer patients undergoing radiotherapy: A prospective randomized clinical trial

Abstract: Abstract. Head and neck malignant tumors have numerous locations of the disease. After patients receive radiotherapy, their nutritional status is very poor, thus the curative effect is unsatisfactory. The aims of the present study were to investigate and analyze the nutritional status of patients with head and neck cancer undergoing radiotherapy (RT) in order to provide positive nutrition intervention for assisting the radiotherapy effect. A total of 40 patients with head and neck cancer were selected using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
1
23
0
8
Order By: Relevance
“…Figures 1 to 5 showed how the nutritional status of patientsgradually declined, and this nutritional deterioration can be seen in both groups. The result was consistent with the study by Kang [ 32 ]. Although nutrition intervention was given to patients who were undernourished, no improvement was seen in their nutrition status.…”
Section: Discussionsupporting
confidence: 94%
“…Figures 1 to 5 showed how the nutritional status of patientsgradually declined, and this nutritional deterioration can be seen in both groups. The result was consistent with the study by Kang [ 32 ]. Although nutrition intervention was given to patients who were undernourished, no improvement was seen in their nutrition status.…”
Section: Discussionsupporting
confidence: 94%
“…As adequate nutritional support is an integral part of a cancer patient’s treatment and malnutrition can complicate the course and outcome of treatment, early intervention of nutritional support is important. Studies have also shown that adequate nutritional support may improve immunocompetence in patients receiving radiation or chemotherapy47–50 and that good nutritional status may increase response rates to therapy and also help to promote better tolerance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The studies suggested that Original Article SMJ early intervention (active dietary counseling, the addition of nutrition supplements, or the use of a prophylactic feeding tube) may improve patients' nutritional statuses. [8][9][10][11] There are a number of ways to manage the nutrition of HNC patients. Many studies have explored effective ways to improve nutrition before, during, and after cancer treatment, especially concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%